South Asia Economic Focus, Fall 2016 : Investment Reality Check - World Bank (Washington, DC: World Bank, 2016)
South Asia defies a sluggish world economy and continues its path of gradual acceleration during 2016. Led by a solid India, the region remains a global growth hot spot. While South Asian economies proved resilient vis-à-vis external headwinds such as China’s slowdown or uncertainty surrounding monetary policy in advanced economies, some are beginning to feel the sting from slowing remittance flows or waning oil price dividends. Against this backdrop of relative stability but fading tailwinds, India is set to grow at 7.6 percent in 2016, the same speed as in 2015, but may increase its pace again in 2017 to 7.7 percent. The region will remain steadfast in the face of future volatility and is expected to grow at 7.1 percent in 2016, however, its medium term performance strongly hinges on investment and exports. Downside risks are concentrated around political uncertainty as well as fiscal and financial vulnerabilities. While export growth is set to return to positive territory, it will deliver only gradually as global demand picks up. A reality check reveals that private investment – the key future growth driver across South Asia – is yet to be ignited to sustain and further increase the pace of economic activity.